Membangun Kesadaran Sosial Siswa Sejak Dini melalui Pendidikan IPS di Sekolah Dasar - Arifin, Iqbal; Hasanah, Uhwah; Hasbahuddin (Celebes Journal of Elementary Education, 2024)
Social Studies (IPS) education at the elementary school level plays a crucial role in fostering students' social awareness from an early age. Social awareness encompasses the ability to understand, appreciate, and interact harmoniously with the social environment, as well as a sense of responsibility toward society. This study reviews the role of Social Studies education in developing social awareness through the application of contextual and value-based learning methods. Learning approaches such as group discussions, simulations, and collaborative projects are utilized to teach social issues such as cultural diversity, social justice, and environmental sustainability. The results indicate that strategically designed Social Studies lessons can shape students into caring, critical individuals who actively contribute to community life. This study recommends strengthening the integration of social values into the Social Studies curriculum to support the development of a socially aware young generation.